El uso de la medicina tradicional y su influencia en la identidad cultural del Cantón Mejía, Provincia de Pichincha - Altamirano Jaguaco, Leydi Melissa (2021)
Traditional medicine is a practice since time immemorial, currently it is used empirically by the healers of the parish of Machachi, this research aims to capture the different cultural manifestations that the parish has among them the traditional medicine, since all practices, The results of this research indicate that the first aborigines of the Machachi valley were the Panzaleos, an indigenous group that migrated due to the arrival of the Spaniards, leaving us the traditional knowledge that they use in the preparation of their medicine thanks to the mother nature that surrounded them. First, a situational diagnosis of the study area was made through the collection of information, revealing that most of the population belongs to rural areas and their main source of income is farming as a means of subsistence, in terms of health services, there is a basic hospital, Despite having three health services, most of the people continue to visit healers to alleviate their ailments, since they mention that they are not only suffering from physical ailments but also from energetic illnesses produced by bad energies that often cannot be explained by medical science. Once the diagnosis was made, we proceeded to an analysis of the people who are dedicated to medicine, giving as a result, that within the parish we found healers and sobadores who currently still continue to practice this profession, there were midwives, unfortunately all have died without being able to transmit their knowledge, in addition to the lack of interest in learning a traditional practice, we proceeded to make an inventory of the cultural manifestations attached to traditional medicine, resulting in 12 existing manifestations in the parish of which are divided; 4 injuries, 4 energetic affections and 4 biological affections, were registered in the INPC cards, in area 4: knowledge and uses related to nature and the universe. At present, they still practice traditional medicine. Finally, after the study carried out, the guide "TRADITIONAL MEDICINE OF THE PARISH OF MACHACHACHI", which consists of 28 pages divided between healers and sobadores, details the materials and the procedure performed by the healer and the sobador according to the condition that is presented.